Lebanon : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Lebanon. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In this study, Lebanon's economy performed well during the global financial crisis. The banking sector has been resilient in the face of the global crisis, thanks to relatively conservative funding and asset structures, and prudent banking regulations and supervision. The need to address the high government debt and to implement growth-enhancing structural reforms is emphasized. To underpin the medium-term fiscal strategy and growth, Executive Directors encouraged the authorities to take the opportunity of the positive economic environment to implement structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet